Teachers’ agency in the implementation of an early childhood education policy program in schools in Bogotá, Colombia - Alba Lucy Guerrero; Marina Camargo-Abello (International Journal of Child Care and Education Policy, 2023)
Abstract The childhood national policy in Colombia recognizes the importance of quality in early childhood education (ECE). In this context, the government of the district of Bogota (2012–2016) proposed the program “Quality preschool in the Public Educational System” to expand the coverage of early education and provide comprehensive care to children aged 3–5 years within the public educational system. This article explores the ways in which the policy program is implemented in schools. Employing an ethnographic approach, this study focuses on the experiences of teachers from five schools that have faced the challenges of integrating the two new grades of early childhood education in formal school settings. By analyzing the educational strategies designed and implemented by teachers in their daily routines and the meaning they assign to these strategies, this study provides evidence that teachers do not simply reproduce the institutionalized discourses; instead, teachers negotiate, resist, adapt, and recreate experiences in relation to school times, spaces, activities, and materials by developing strategies more responsive to children’s needs. The concept of agency is central to understand how teachers end up generating practices that lead to new forms of individual and social transformation.